Durability of CNS disease control in NSCLC patients with brain metastases treated with immune checkpoint inhibitors plus cranial radiotherapy. (June 2021) - Lau, Sally C.M.; Poletes, Christopher; Le, Lisa W.; Mackay, Kate M.; Fares, Aline Fusco; Bradbury, Penelope A.; Shepherd, Frances A.; Tsao, Ming Sound; Leighl, Natasha B.; Liu, Geoffrey; Shultz, David; Sacher, Adrian G.
Highlights: The activity of immune checkpoint inhibitors (ICI) against NSCLC brain metastases is unknown. We compared CNS outcomes between ICI- and chemo-treated patients who have received brain RT. ICI-treated patients were less likely to have CNS involvement at the time of systemic progression. Intracranial PFS was superior in patients treated with brain RT and ICI. Cumulative incidence of CNS progression was significantly less in patients with PD-L1 ≥ 50 %. Abstract: Background: Immune checkpoint inhibitors (ICIs) have excellent systemic activity and are standard first line treatment in EGFR/ALK wild type metastatic non-small cell lung cancer (NSCLC). However, their role in patients with brain metastases, which affects over 20% of patients and cause significant morbidity, is less clear. Methods: We reviewed patients with EGFR / ALK wild-type mNSCLC with CNS metastases. Serial MRIs were reviewed to determine the time to intracranial progression (iPFS). Multivariate regression was performed to adjust for the disease-specific graded prognostic score (ds-GPA). Results: We identified 36 ICI- and 33 chemotherapy-treated patients with baseline CNS metastases and available serial MRIs (average frequency:3.5 months). Baseline radiation was given except for 2 chemotherapy-treated patients with asymptomatic solitary metastasis. The CNS burden of disease was higher in the ICI-treated group (ICI:22% vs. chemotherapy:0% had >10 lesions; p = 0.02), but the utilization of WBRT was not (ICI:31% vs. chemotherapy:45%; p = 0.09). At the time of progression, CNS involvement was identified in 30 % of ICI-treated patients compared to 64 % of chemotherapy controls (p = 0.02). ICI-treated patients had superior iPFS (13.5 vs 8.4 months) that remained significant in multivariate analysis (HR 1.9; 95%CI 1.1-–3.4). Superior CNS outcomes in ICI-treated patients were driven by the PD-L1 high subgroup where the 12-month cumulative incidence rate of CNS progression was 19% in ICI-treated PD-L1 ≥ 50%, 50% in ICI-treated PD-L1 < 50% and 58% in chemotherapy-treated patients (p = 0.03). Conclusions: Remarkable CNS disease control is seen with baseline RT plus ICIs in patients with PD-L1 ≥ 50%. Strategies for delaying WBRT should be investigated in this subgroup of patients.